Repeated Templating - Tiemann, Michael (Chemistry of Materials)
In recent years, a lot of research activity has focused on the synthesis of new ordered porous materials by utilization of porous matrices as templates. Since the matrices are themselves created by templating procedures, the entire process can be envisaged as “repeated templating”. This review describes recent conceptual developments in the field of structure replication and summarizes the large number of publications on new functional materials prepared by this method.